(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Tashkent city’s transport system is playing an important role in responding to urbanization and the growing needs of the population. The organization of separate traffic lanes for buses is an important step in improving the efficiency of city transport and ensuring road safety. This article provides a comprehensive analysis of the status of bus routes in Tashkent, their organization, effectiveness, problems and prospects.